Hubungan Status Ekonomi dan Dukungan Keluarga Dengan Pemilihan Penolong Persalinan di Wilayah Kerja Puskesmas Sukarami - Putu Lusita Nati Indriani; Novy Aryani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Ministry of Health's policy in the last decade emphasizes that every birth should be assisted by health personnel in order to reduce maternal and infant mortality. According to the 2019 South Sumatra Health Profile the number of maternal deaths in Muara Enim Regency in 2019 was 43 cases. Meanwhile, infant mortality in Muara Enim Regency in 2019 was 289 per 1,000 live births. This study aims to determine the relationship between economic status and family support with the labor help in the Sukarami Public Health Center, Muara Enim Regency in 2021. This type of research is analytic with quantitative methods using a cross sectional approach. The results showed that out of 38 respondents with high economic status, 26 respondents (68.4%) chose birth attendants who were health workers and 12 respondents (31.6%) were chose not health workers. Meanwhile, out of 27 respondents with low economic status, 11 respondents (40.7%) chose birth attendants who were health workers and 16 respondents (59.3%) were chose not health workers. Furthermore, of the 35 respondents with good family support, 25 respondents (71.4%) chose health worker birth attendants and 10 people (28.3%) were chose not health workers. Meanwhile, out of 30 respondents with poor family support, 12 respondents (40%) chose health worker birth attendants and 18 people (60%) were chose not health workers. The conclusion from this study is that there is a relationship between economic status and family support simultaneously with the labor help in the Sukarami Health Center, Muara Enim Regency in 2021.